A Multi-species World in the Poetry of Alenka Jovanovski and Vesna Liponik - Golež Kaučič, Marjetka (Poznańskie Studia Slawistyczne, 2022)
The article examines selected poems that deal with the inter-species relations in a multi-species world, from the collections of poems Tisoč osemdeset stopinj (Thousand Eighty Degrees) by Alenka Jovanovski and roko razje (Eats Away the Hand) byVesna Liponik. Through the analysis and interpretation, we investigate how their poetics work when it collides with the demonization of the other and the overt or covert social and environmental speciesism. In doing so, we discuss the symbolic and active power of poetry, the poets’ critique of the binary divide between man and other beings, and their emphasis on the inherent value of animal and, in awider context, their political-economic critique of global capitalism and linguistic, symbolic, material human violence against other species and nature.